Care and Repair of Advanced Composites - Keith B Armstrong (author), William Cole (author), Eric Chesmar (author), Francois Museux (author) (SAE International, 2020)
Introduction to advanced manufacturing was written by two experienced and passionate engineers whose mission is to make the subject of advanced manufacturing easy to understand and a practical solution to everyday problems. Harik, Ph.D. and Wuest, Ph.D., professors who have taught the subject for decades, combined their expertise to develop both an applied manual and a theoretical reference that addresses many different needs. -- Provided by publisher.